2002
DOI: 10.1152/jn.00693.2001
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity and Spatial Distribution of Signals From the Receptive Field Surround in Macaque V1 Neurons

Abstract: Selectivity and spatial distribution of signals from the receptive field surround in macaque V1 neurons. J Neurophysiol 88: 2547-2556, 2002; 10.1152/jn.00693.2001. The responsiveness of neurons in V1 is modulated by stimuli placed outside their classical receptive fields. This nonclassical surround provides input from a larger portion of the visual scene than originally thought, permitting integration of information at early levels in the visual processing stream. Signals from the surround have been reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
450
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(504 citation statements)
references
References 21 publications
(27 reference statements)
48
450
6
Order By: Relevance
“…Two forms of suppression have been isolated in the primary visual cortex of cats and monkeys. One is "surround suppression," in which the mask has the orientation preferred by the neuron but is presented outside the receptive field (DeAngelis et al, 1994;Cavanaugh et al, 2002). The other is "overlay suppression," in which the mask is presented within the receptive field (superimposed on the test) and can have any orientation (Morrone et al, 1982;Bonds, 1989;DeAngelis et al, 1992;Carandini et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Two forms of suppression have been isolated in the primary visual cortex of cats and monkeys. One is "surround suppression," in which the mask has the orientation preferred by the neuron but is presented outside the receptive field (DeAngelis et al, 1994;Cavanaugh et al, 2002). The other is "overlay suppression," in which the mask is presented within the receptive field (superimposed on the test) and can have any orientation (Morrone et al, 1982;Bonds, 1989;DeAngelis et al, 1992;Carandini et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The difference is in the modulation by surrounding elements, hence it could tune neurons to a graded specialization for processing junctions [18,4]. Typically the surround influence was suppressive when the surround grating was at the neuron's preferred orientation [3], but when the orientation in the surround was perpendicular to the preferred orientation facilitation became evident. Neural responses to crossings were on average more than 3 times stronger [16], but they also respond to a grating or a single bar of a preferred orientation [18,16,3,7].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports [18,16,3,7] have demonstrated that the responsiveness of neurons in V1 is modulated by stimuli placed outside their CRFs. Cells with suppressive surround influence corresponding to surround orientation of a grating or bar pattern at the neuron's preferred orientation were found.…”
Section: Crossing Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, data from (Cavanaugh et al 2002) suggest that the surround size depends on the receptive field size of V1 simple cells. In order to be consistent with these findings, we first decompose the image into many scales using the Laplacian pyramid.…”
Section: Overcoming the Global Surround Constraintmentioning
confidence: 99%